International aspects of organizational ethics in educational systems - Shapira-Lishchinsky, Orly (Studies in educational administration., 2018)
This book takes a unique organizational approach towards understanding the concept of ethics in educational systems. It provides a global perspective and connects theory and praxis through team-based simulations, case studies and scenarios, thus presenting an integrative approach towards tackling teachers' withdrawal behaviors.